Conceptualising the Primary to Secondary School Transition within the Theoretical Framework of Ecosocial Theory - Donaldson, Caitlyn; Moore, Graham; Hawkins, Jemma (International Journal of Educational and Life Transitions, 2023)
The transition between primary and secondary school is an important event in the lives of young people with the potential to impact mental health outcomes in the short and long term. This paper argues that ecosocial theory, a theory of epidemiology, offers important insights into the relationship between students, schools and mental health across the transition process. It draws on theoretical perspectives on psychosocial and flexible resource distribution, contending that low socio-economic status is associated with lower resources, resulting in greater risk of a problematic transition experience. It also highlights that the school environment may affect how stressful the transition process is for young people, influencing levels of school connectedness and sense of belonging post-transition. The paper concludes by considering how critical realism, in its ontological realism and epistemological relativism, offers an important research paradigm from which to research school transition and mental health.
Keywords: Ecosocial theory; mental health; school transition; critical realism; socioeconomic status